Self‐Supporting Electrocatalyst Film Based on Self‐Assembly of Heterogeneous Bottlebrush and Polyoxometalate for Efficient Hydrogen Evolution Reaction. Issue 14 (13th February 2022) - Lin, Yayu; Zhu, Youlong; Ma, Qian; Ke, Xianlan; Ma, Pengwei; Liao, Rongfeng; Liu, Shaohong; Wu, Dingcai
Abstract: Developing efficient electrocatalysts to promote the hydrogen evolution reaction (HER) is essential for a green and sustainable future energy supply. For practical applications, it is a challenge to achieve the self‐assembly of electrocatalyst from microscopic to macroscopic scales. Herein, a facile strategy is proposed to fabricate a self‐supporting electrocatalyst film (CNT‐ g ‐PSSCo/PW12 ) for HER by electrostatic interaction‐induced self‐assembly of cobalt polystyrene sulfonate‐grafted carbon nanotube heterogeneous bottlebrush (CNT‐ g ‐PSSCo) and polyoxometalate (PW12 ). Co 2+ ions of CNT‐ g ‐PSSCo can function as junctions for interconnecting neighboring bottlebrushes to form the 3D nanonetwork structure and enable electrostatic capture of negatively charged PW12 nanodots. Moreover, CNT backbones can provide highly conductive pathways to CNT‐ g ‐PSSCo/PW12 . Such a self‐assembled CNT‐ g ‐PSSCo/PW12 displays a low overpotential of 31 mV at a current density of 10 mA cm −2 and a small Tafel slope of 25 mV dec −1, showing high efficiency toward HER. Furthermore, CNT‐ g ‐PSSCo/PW12 with a stable self‐supporting film morphology exhibits long‐term electrocatalytic stability over 1000 CV cycles without noticeable overpotential change in acidic media. The findings may provide a new avenue for constructing self‐assembled functional nanonetwork materials with well‐orchestrated structural hierarchy for many applications in energy, environment, catalysis, medicine, and others. Abstract : Self‐supporting CNT‐ g ‐PSSCo/PW12 film with a 3D hierarchical nanonetwork structure has been successfully fabricated by a facile electrostatic interaction‐induced self‐assembly strategy. As hydrogen evolution reaction (HER) electrocatalyst, CNT‐ g ‐PSSCo/PW12 displays highly catalytic activity (an ultralow overpotential of 31 mV), fast reaction kinetics (a small Tafel slope of 25 mV dec −1 ), and long‐term stability (almost unchanged overpotential over 1000 CV cycles).